Implementasi Pemberdayaan Ekonomi Perempuan Miskin Desa Melalui Kegiatan Simpan Pinjam Syariah di Koperasi Wanita Makmur Sejati - Sumiati; Koesoemaningsih, Rachmawati; Sugiyanto, Lina (Universitas Dr. Soetomo Surabaya, 2024)
This research aims to describe the implementation of women's economic empowerment carried out by the Makmur Sejati Women's Cooperative, as well as the problems it faces. The research was conducted using a descriptive qualitative approach. Data were collected through interviews, documentation, and literature. The data that has been collected is analyzed interactively until completion. Data triangulation is carried out with source triangulation. The research shows that the sharia savings and loan activities carried out by the Makmur Sejati Women's Cooperative have been able to contribute well to the improvement of micro businesses undertaken by poor women in Karangjati Village, marked by an increase in income and investment as well as the quality of women's human resources. With this economic empowerment activity, women in Karangjati Village have played a role in fulfilling their family's economic welfare. On the other hand, there are obstacles faced in the empowerment process, among others: the lack of qualified human resources of the cooperative management, the existence of loan funds that are not in accordance with their uses, and the existence of members who are not smooth in making installments. The sharia savings and loan program run by the Makmur Sejati Women's Cooperative is in accordance with Islamic economic principles and DSN Fatwa No. 15/DSN-MUI/IX/2000 in terms of: calculation of mudarabah financing and calculation of the ratio distribution.